If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying sqrt(x + 23) + sqrt(2 + -1x) = sqrt(-2x + -1) Reorder the terms: qrst(23 + x) + sqrt(2 + -1x) = sqrt(-2x + -1) (23 * qrst + x * qrst) + sqrt(2 + -1x) = sqrt(-2x + -1) (23qrst + qrstx) + sqrt(2 + -1x) = sqrt(-2x + -1) 23qrst + qrstx + (2 * qrst + -1x * qrst) = sqrt(-2x + -1) 23qrst + qrstx + (2qrst + -1qrstx) = sqrt(-2x + -1) Reorder the terms: 23qrst + 2qrst + qrstx + -1qrstx = sqrt(-2x + -1) Combine like terms: 23qrst + 2qrst = 25qrst 25qrst + qrstx + -1qrstx = sqrt(-2x + -1) Combine like terms: qrstx + -1qrstx = 0 25qrst + 0 = sqrt(-2x + -1) 25qrst = sqrt(-2x + -1) Reorder the terms: 25qrst = qrst(-1 + -2x) 25qrst = (-1 * qrst + -2x * qrst) 25qrst = (-1qrst + -2qrstx) Solving 25qrst = -1qrst + -2qrstx Solving for variable 'q'. Move all terms containing q to the left, all other terms to the right. Add 'qrst' to each side of the equation. 25qrst + qrst = -1qrst + qrst + -2qrstx Combine like terms: 25qrst + qrst = 26qrst 26qrst = -1qrst + qrst + -2qrstx Combine like terms: -1qrst + qrst = 0 26qrst = 0 + -2qrstx 26qrst = -2qrstx Add '2qrstx' to each side of the equation. 26qrst + 2qrstx = -2qrstx + 2qrstx Combine like terms: -2qrstx + 2qrstx = 0 26qrst + 2qrstx = 0 Factor out the Greatest Common Factor (GCF), '2qrst'. 2qrst(13 + x) = 0 Ignore the factor 2.Subproblem 1
Set the factor 'qrst' equal to zero and attempt to solve: Simplifying qrst = 0 Solving qrst = 0 Move all terms containing q to the left, all other terms to the right. Simplifying qrst = 0 The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined.Subproblem 2
Set the factor '(13 + x)' equal to zero and attempt to solve: Simplifying 13 + x = 0 Solving 13 + x = 0 Move all terms containing q to the left, all other terms to the right. Add '-13' to each side of the equation. 13 + -13 + x = 0 + -13 Combine like terms: 13 + -13 = 0 0 + x = 0 + -13 x = 0 + -13 Combine like terms: 0 + -13 = -13 x = -13 Add '-1x' to each side of the equation. x + -1x = -13 + -1x Combine like terms: x + -1x = 0 0 = -13 + -1x Simplifying 0 = -13 + -1x The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined. The solution to this equation could not be determined.
| 18/5a=3/5 | | 16/11*-18/36 | | y=100+8.25x | | -7/8-1/2= | | 10x-36=180 | | 6/7=3z/42 | | 5(2x+1)-7(x-2)=-1 | | x+(x+1)+(x*2)=29 | | x^3+0.6x^2-13.4x+3.9=0 | | 2x+21-6x=5 | | 25xy^2/15y | | 3n^2=14+n | | -6(x-6)+7=43 | | x^2/3=49 | | 7/9y-28=70 | | 6v+5(5+4v)=155 | | 4x^3+28x^2+48x=0 | | -36/(-4)= | | 2w^2-10w+12=0 | | -9(-2+6n)=504 | | 2-8a=-5 | | 5/3 | | 2x+45=65 | | (5/6)/3 | | x=x^3-3x^2+5 | | 111=-3(8x+3) | | 3x-14x=0 | | 5/6/3= | | 2(7+4n)=-10 | | x^3+6x^2+9x=x^2+11x+24 | | -6(x+4)=114 | | 30+2n=6(5+6) |